Teachers’ job satisfaction as mediator of the relationship between teachers’ motivation and teachers’ work performance: Survey from secondary schools in Sarawak - Evonne Lai Eng Fei; Crispina Gregory K Han (Asian Scholars Network, 2019)
This paper investigates the potential mediating role of teachers’ job satisfaction between teachers’ motivation and teachers; work performance. A survey technique and random sampling technique (ratio) were used to collect 2738 respondents from Secondary Schools in Sarawak. The instruments used were The Work Tasks Motivation Scale for Teachers (WTMST), Minnesota satisfaction Questionnaire (MSQ) and Teachers’ Job Performance Self-rating questionnaire (TJPSQ) with 5-points Likert scale. Smart-PLS measurement and structural model were the procedures used to asses and evaluate the statistical significance of relevant path coefficients. The findings showed that the teaching task, additional task and administrative task have increased extrinsic and intrinsic satisfaction. Thus, this will improve teachers’ performance more effectively because they have appropriate tasks in their working environment.